Predominant prevalence of human rotaviruses with the G1P[8] and G8P[8] genotypes with a short RNA profile in 2013 and 2014 in Sukhothai and Phetchaboon provinces, Thailand. Issue 4 (7th September 2016) - Guntapong, Ratigorn; Tacharoenmuang, Ratana; Singchai, Phakapun; Upachai, Sompong; Sutthiwarakom, Karun; Komoto, Satoshi; Tsuji, Takao; Tharmaphornpilas, Piyanit; Yoshikawa, Tetsushi; Sangkitporn, Somchai; Taniguchi, Koki
Abstract : Of 2, 754 stool specimens collected from children with acute gastroenteritis during 2013–2014 in Sukhothai and Phetchaboon provinces, Thailand, 666 (24.2%) were positive for rotavirus A (RVA) in polyacrylamide gel electrophoresis (PAGE). The G and P types of all RVA‐positive specimens were determined by semi‐nested RT‐PCR. G1P[8] (56.5%) was most prevalent, followed by G2P[4] (22.1%). Unusual G8P[8] human RVAs (HuRVAs) were detected at a high frequency (20.0%). Interestingly, 171 of the 376 G1P[8] HuRVAs and all of the 133 G8P[8] HuRVAs showed a short RNA pattern in PAGE. Thus, it was shown that the properties of HuRVAs have been markedly unusual in recent years in Thailand. J. Med. Virol. 89:615–620, 2017 . © 2016 Wiley Periodicals, Inc.